2021
DOI: 10.37859/mrabj.v2i2.2427
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Public Service Motivation dan Kepuasan Kerja Terhadap Kinerja Pegawai

Abstract: Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh public service motivation dan kepuasan kerja terhadap kinerja pegawai di kantor catatan sipil (Capil) Kabupaten Konawe Selatan. Penelitian ini merupakan penelitian kuantitatif dengan mengambil sampel pada 65 pegawai non PNS pada Kantor Capil Kabupaten Konawe Selatan. Metode analisis data yang digunakan adalah analisis regersi linear berganda. Berdasarkan hasil penelitian ditemukan bahwa public service motivation dan kepuasan kerja secara simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
1
0
4
Order By: Relevance
“…Valence includes each officer's assessment of the extent to which the rewards from the results of HSK inspection work are considered positive or negative and the extent to which the rewards can fulfill their desires. So it is in accordance with other research which states that the rights obtained can improve employee performance (Hamid, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Valence includes each officer's assessment of the extent to which the rewards from the results of HSK inspection work are considered positive or negative and the extent to which the rewards can fulfill their desires. So it is in accordance with other research which states that the rights obtained can improve employee performance (Hamid, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…If the p value is obtained < 0.05 and the statistical T > 1.96 (t value two tail, α 5%), it is concluded that the exogenous variable has a significant effect on endogenous with the direction of influence according to the sign attached to the path coefficient. Furthermore, if the p value is obtained > 0.05 and the statistical T < 1.96 (t value two tail, α 5%), then it is concluded that the exogenous variable has no significant effect on endogenous (Adnan Hakim, 2021). Based on the test results of Table 6, the following results were obtained (1) Leadership style has no effect on KIN, indicated by sig = 0.124 > 0.05 and statistical T 1.156 < 1.96, this means that the high and low GK does not affect the high and low KIN.…”
Section: Figure 2 Pls Bootstrapping Model Estimation Results 500 Samp...mentioning
confidence: 97%
“…Kondisi kerja yang ideal perlu diciptakan oleh organisasi sehingga dapat mendorong pegawai untuk meningkatkan keterampilan, salah satunya yaitu dengan menciptakan kepuasan kerja pegawai. Kepuasan kerja yaitu keadaan emosi seseorang yang menyenangkan dan positif yang berasal dari penilaian suatu pekerjaan atau pengalaman kerja (Hakim & Hamid, 2021). Beberapa penelitian memandang kepuasan kerja sebagai topik atau studi yang penting dan berpengaruh terhadap kinerja dan kualitas pelayanan (Lu & Chen, 2022).…”
Section: Abstrakunclassified
“…Menurut Hakim & Hamid (2021) kepuasan kerja berkorelasi dengan motivasi pelayanan publik. Motivasi pelayanan publik ialah kecenderungan seseorang atau individu dalam merespons motif secara unik yang berada di lingkup organisasi sektor publik (Perry & Wise, 1990).…”
Section: Abstrakunclassified